HUBUNGAN HIPERURISEMIA, OBESITAS DAN RIWAYAT MEROKOK DENGAN KEJADIAN HIPERTENSI - Eso, Amirudin; Hamra, M. Yusuf; Ahmadi, Adhytya Pratama (Medula, 2013)
Hypertension is a common clinical problem. Hyperuricemia, obesity, and smoking history are assumed to have  a  relationship  with  hypertension  in  adult.  This  study  was  conducted  to  figure  out  the  association  between hyperuricemia, obesity and smoking history with hypertension. Observational method with cross-sectional approach was used in this study. The study was conducted in Laboratorium Klinik Prodia Kendari. Sixty-two samples consist of men and women aged 18-65 years were taken by quota sampling. Blood pressure, body mass index, and blood chemistry result were collected during medical check-up. Smoking history data was collected with direct interview. Chi-square  and  binary  logistic  regression  analysis  were  used  to  analyze  the  data  (α=0,05).  There  were  50% hypertensive  subjects  and  50%  non-hypertensive  subjects.  Hyperuricemia  had  a  moderate  association  with hypertension (p=0,000; r=0,455). Obesity had a weak association with hypertension (p=0,020 ; r=0,248). Smoking history  also  had  a  weak  association  with  hypertension  (p=0,022  ;  r=0,279).  In  multivariate  analysis  with confounding factors, only hyperuricemia that had an independent influence to hypertension (p= 0,00 ; OR 25,4 ; 95% CI 4,1-156,1), followed by HDL abnormality (p=0,04 ; OR=14,15 ; 95% CI=2,3-84,2) and total cholesterol (p=0,02  ;  OR=22,4  ;  95%  CI=3,2-153,8).  Hyperuricemia,  obesity,  and  smoking  history,  were  associated  with hypertension. Only hyperuricemia had the independent influence to hypertension. Key words: Hyperuricemia, obesity, smoking history, hypertension